Nursing students’ perception toward their learning environment - Samson, Priscilla; Pun, Khagi Maya; Poudel, Ambika; Panthee, Bimala (Journal of Patan Academy of Health Sciences, 2021)
Introduction: The quality of the learning environment is indicative of the effectiveness of an educational program on student learning, motivation, and learning outcomes. Students' perception of their learning environment may act as a basis for making necessary modifications for ensuring quality assurance. This study aimed to assess the perception of nursing students towards their learning environment. Method: An analytical cross-sectional study was conducted in May 2020 among nursing students from Patan Academy of Health Sciences, Lalitpur, Nepal. Dundee Ready Education Environment Measure (DREEM) inventory was used for an online survey via Google form. Descriptive analysis was used to calculate students' learning perception; a one-way ANOVA was used to analyze the difference across four programs. The difference between first and final-year students' perceptions was tested using a t-test. Result: Out of 289 participants, 200(69.2%) perceived their learning environment as more positive than negative. The mean score was 142.64 on the DREEM global score of 200. There was a significant difference in the perceptions in all the subscales across four nursing programs (p<0.05) except in the learning subscale (p=0.24). There was a significant difference in perception between first and final-year students across five subscales (p<0.05) except for social self-perception (p=0.85). Conclusion: The study revealed that more than half of the nursing students perceived their learning environment as more positive than negative. There was a statistically significant difference in perception across all the nursing programs and between first and final-year students.